Comparison of cognitive decline between dementia with Lewy bodies and Alzheimer's disease: a cohort study. Issue 1 (8th February 2012) - Walker, Zuzana; McKeith, Ian; Rodda, Joanne; Qassem, Tarik; Tatsch, Klaus; Booij, Jan; Darcourt, Jacques; O'Brien, John
Abstract : Objectives: Dementia with Lewy bodies (DLB) accounts for 10%–15% of dementia cases at autopsy and has distinct clinical features associated with earlier institutionalisation and a higher level of carer distress than are seen in Alzheimer's disease (AD). At present, there is on-going debate as to whether DLB is associated with a more rapid cognitive decline than AD. An understanding of the rate of decline of cognitive and non-cognitive symptoms in DLB may help patients and carers to plan for the future. Design: In this cohort study, the authors compared 100 AD and 58 DLB subjects at baseline and at 12-month follow-up on cognitive and neuropsychiatric measures. Setting: Patients were recruited from 40 European centres. Participants: Subjects with mild–moderate dementia. Diagnosis of DLB or AD required agreement between consensus panel clinical diagnosis and visual rating of 123I-FP-CIT (dopamine transporter) single photon emission computed tomography neuroimaging. Outcome measures: The Cambridge Cognitive Examination including Mini-Mental State Examination and Neuropsychiatric Inventory (NPI). Results: The AD and DLB groups did not differ at baseline in terms of age, gender, Clinical Dementia Rating score and use of cholinesterase inhibitors or memantine. NPI and NPI carer distress scores were statistically significantly higher for DLB subjects at baseline and at follow-up, and there were no differences between AD and DLB in cognitive scores at baseline or at follow-up. There was no significant difference in rate of progression of any of the variables analysed. Conclusions: DLB subjects had more neuropsychiatric features at baseline and at follow-up than AD, but the authors did not find any statistically significant difference in rate of progression between the mild–moderate AD and DLB groups on cognitive or neuropsychiatric measures over a 12-month follow-up period.